Methodology for post-event analysis of flash floods – Svacenický Creek case study - BLAŠKOVIČOVÁ, Lotta; HORVÁT, Oliver; HLAVČOVÁ, Kamila; KOHNOVÁ, Silvia; SZOLGAY, Ján (Contributions to Geophysics and Geodesy, 2011)
In this paper a methodology for a post-event analysis of a flash flood and estimation of the flood peak and volume are developed and tested. The selected flash flood occurred on the 6th of June, 2009 in the Svacenický Creek Basin. To understand rainfallrunoff processes during this extreme flash flood, the runoff response was simulated using the spatially-distributed hydrological model KLEM (Kinematic Local Excess Model). The distributed hydrological model is based on the availability of raster information about the landscape’s topography, soil and vegetation properties and radar rainfall data. In the model, the SCS-Curve Number procedure is applied to a grid for the spatially-distributed representation of the runoff-generating processes. A description of the drainage system’s response is used to represent the runoff’s routing. The simulated values achieved by the KLEM model were comparable with the maximum peak estimated on the basis of the post-event surveying. The consistency of the estimated and simulated values from the KLEM model was evident both in time and space, and the methodology has shown its practical applicability.